The role of religion in work-life interface. Issue 22 (16th December 2019) - Sav, Adem
Abstract: Although religion is central to the lives of many people, little attempt has been made to understand its role within work–life conflict, work–life facilitation and more broadly, work–life balance. This study advances current knowledge by examining the role of religion within these concepts, and exploring its moderator influence. This is achieved through investigating the experiences of Australian Muslim men and the religion of Islam, which encourages multiple roles for its followers and involves well-defined physical acts of worship. To test various hypotheses, data were collected in the form of survey questionnaires, either face-to-face or online, from 301 Australian Muslim men. The findings support the proposition that religiosity can be beneficial for work–life balance, rather than competing with work and other non-work roles for time and energy. Furthermore, religiosity can moderate the relationships between job demands and work-to-life conflict, and work hours and work-to-life conflict, but not between work flexibility and work/life facilitation, and family demands and life-to-work conflict. The findings suggest that religiosity can be important for work–life balance and stress the need for a change in research direction in this area, one that is broadened to include other roles besides work and family, including religion.